Biomechanical Comparison of 2 Different Femoral Stems in the Shortening Osteotomy of the High-Riding Hip - Tuncay, Ibrahim; Yildiz, Fati̇h; Bilsel, Kerem; Uzer, Gökçer; Elmadag, Mehmet; Erden, Tunay; Bozdag, Ergun (Elsevier BV, 2016)
We hypothesized that a rectangular cross-sectional femoral stem may produce more initial stability of the transverse subtrochanteric femoral shortening osteotomy rather than a circular cross-sectional stem.Twenty, fourth-generation, synthetic femur models were inserted with either circular or rectangular cross-sectional femoral stems after 3 cm of transverse subtrochanteric shortening. Half of the models were tested with axial bending and the other half with torsional loads. After the femora underwent cyclic loading, they were loaded until failure. Outcome parameters were stiffness values before and after cyclical loading, failure loads/torques, and displacements at the osteotomy sites.In axial bending tests, the results were not significantly different between the groups. Under rotational forces, the mean stiffness value before cyclical loading and failure torque of the cylindrical stems was significantly higher than that of rectangular cross-sectional stems (11.8 ± 1.2 vs 7.1 ± 2.8 Nm/degree; P = .009 and 136.9 ± 60.2 vs 27.1 ± 17.5 Nm; P = .027 Nm, respectively). The mean amounts of displacements at the osteotomy sites were not significantly different between the groups in any direction in both axial and rotational tests.According to the results of the study, using straight, cylindrical femoral stems can increase rotational stability of the transverse osteotomy more than the rectangular cross-sectional stems although the latter one has the advantages of rectangular geometrical design.
Keywords: Hip; Torque; Arthroplasty, Replacement, Hip; Posture; Humans; Equipment Design; Femur; Stress, Mechanical; Biomechanical Phenomena; Osteotomy